An action research project on enhancing student’s awareness of British Culture in speaking lessons at a secondary school in Quang Binh - Hoàng, Thị Thu Giang (2020)
Regarding the importance of intercultural competence in second language acquisition, progressive scholars today believe that culture and language are inseparable and culture elements must be an integral part of language learning. Admittedly, language is a means of transporting culture and cultural elements present in every aspect of language. Mastering a target language means to understand its distinctive culture. It is a commonly held belief that the integration of target cultural knowledge into lessons have had positive effectiveness on enhancing student’s awareness of culture. This action research project applied a trial intensive speaking course specifying the eight stated British cultural elements. Consequently, the applied cultural teaching techniques together with productive students’ speaking practice activities widened students’ knowledge of British culture. The intercultural communicative competence of students, to some extent, has been improved.